Karl Mannheim and the Power of Sociology: Reflexivity, Plurality and the Diagnosis of the Present (Simbiótica. Revista Eletrônica, 2025)
This review examines the recent French publication of Karl Mannheim’s 1930 general sociology course, translated and introduced by Dominique Linhardt. The ten lectures provide a unique window into Mannheim’s pedagogical method and the emergence of sociological reflexivity during the crisis of the Weimar Republic. The review reconstructs Mannheim’s analysis of the socio-historical conditions that gave rise to modern reflexivity, the role of class differences in shaping worldviews, and the development of the sociology of knowledge as a critical response to increasing social differentiation and the collapse of unified meaning. I argue that the contemporary relevance of the course lies in Mannheim’s ability to combine criticism, historicization and openness to complexity, offering a conceptual framework to understand both the contemporary resurgence of regressive attitudes and the paradoxes of what I call reflexive post-modernity
Keywords: Karl Mannheim; sociology of knowledge; modernity; reflexivity; reflexive post-modernity